PEREMPUAN PEMBAWA SIAL PRESPEKTIF IBN BAṬṬĀL DAN AHMAD FUDHAILI: TELAAH HADIS ṢAḤĪḤ AL-BUKHĀRĪ NO. 2646: THE WOMAN AS A BEARER OF MISFORTUNE IN THE PERSPECTIVES OF IBN BAṬṬĀL AND AHMAD FUDHAILI: A STUDY OF ḤADITH ṢAḤĪḤ AL-BUKHĀRĪ NO. 2646 - Abil Ash; Muhammad Awfa Munawar; Jaya Rukmana; Ajeng Ayu (Al-Ma‘ani: Journal of Islamic Studies, 2025)
This study examines the hadith concerning misfortune associated with women in Ṣaḥīḥ al-Bukhārī by comparing the interpretations of Ibn Baṭṭāl and Ahmad Fudhaili in order to understand its meaning in a more contextual and proportional manner. This research employs a qualitative method based on library research. Primary data are obtained from authoritative hadith collections such as Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, while secondary data include supporting literature such as Qur’anic exegesis, hadith commentaries, and academic journals. Data collection techniques involve examining hadith texts, identifying the sanad (chain of transmission) and matn (text of the hadith), and analyzing both classical and contemporary interpretations. The findings show that the interpretation of women as bearers of misfortune is more socio-cultural than theological in nature. Ibn Baṭṭāl interprets the hadith literally while still considering contextual possibilities. In contrast, Ahmad Fudhaili firmly rejects misogynistic interpretations and emphasizes a more humane and just interpretive approach. Therefore, interpretations that marginalize women should be critically reexamined to align with Islamic values of justice, equality, and humanity.